Solve the Following Equation: ("A" + 5)/6 - ("A" + 1)/9 = ("A" + 3)/4 - Mathematics

Advertisement Remove all ads
Sum

Solve the following equation:

`("a" + 5)/6 - ("a" + 1)/9 = ("a" + 3)/4`

Advertisement Remove all ads

Solution

Since, L.C.M. of denominators 6,9 and 4 = 36

∴ `("a" + 5)/6 xx 36 - ("a" + 1)/9 xx 36 = ("a" + 3)/4 xx 36`
  ...(Multiplying each term by 36)

⇒ 6(a + 5) - 4(a + 1) = 9(a + 3)

⇒ 6a + 30 - 4a - 4 = 9a + 27

⇒ 6a - 4a - 9a = 27 - 30 + 4

⇒ 6a - 13a = 1

⇒ -7a = 1

⇒ a = `-1/7`

Concept: Simple Linear Equations in One Variable
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 14 Linear Equations in one Variable
Exercise 14 (A) | Q 14 | Page 165
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×